Ответы и объяснения

2013-09-10T16:12:44+00:00
4(3-х)-11=7(2х-5)
12-4х-11=14х-35
-4х-14х= -35-12+11
-18х= -36
х=2
Лучший Ответ!
2013-09-10T16:14:02+00:00
4(3-х)-11=7(2х-5)                                                                                                       12-4х-11=14х-35                                                                                                       -4х-14=-35-12+11                                                                                                      -18х=-36                                                                                                                      х=2